Mixed mode I + II interlaminar fracture of glass/epoxy multidirectional laminates - Part 2: Experiments - Pereira, A. B.
Mixed-mode bending (MMB) tests were performed on glass/epoxy multidirectional specimens with delaminations in 0/theta and theta/-theta type interfaces. The initiation mode I and mode II strain energy release rates (G(I) and G(II)) were obtained from the modified beam theory (MBT) data reduction scheme presented in part 1. Measured compliances agreed well with MBT predictions. Critical energy release rate G, versus G(II)/G fracture loci were built with results of MMB, double cantilever beam (DCB) and end notched flexure (ENF) tests. In spite of some discrepancies, fracture loci appeared to be linear. G(c) values increased moderately with theta for both 0/theta and theta/-theta interfaces.